A Novel Equation for Quality in Education? - Chamas, Mohamad; Polonik, Irina (Archives of Business Research, 2020)
Nowadays educational organizations are facing an increasing dependence of university budgets on the financial market and the application of new financial instruments so that the financial department has become the most powerful, especially in the university. Following Ginsberg [1] and Engelen et al [2], we can speak of a trend toward a kind of financialization of the university Universities have been increasingly concerned to demonstrate their contribution to the economic performance of their local and national economies. Worldwide, a big part of educational organizations is doing a major effort by examining students’ services and creating student-friendly approaches that far exceed customer service. This trend is nominated ‘the art of capturing audiences and entertaining them’ following Arum and Roksa [3]. In this study, the authors aim to find out if factors related to industrialization and innovation can influence the quality of educational organizations, and if yes what is the equation that links all these factors. A questionnaire was administered to students, teachers, and guardians. Responses were analyzed using the linear regression model. Based on the statistical analysis, the authors create an innovative scientific equation that links all the significant factors that could affect the quality of educational services. This equation could be used by educational organizations to assess their quality level.